Respuesta :

Answer:

49

Step-by-step explanation:

10-9+8×6÷(5-2^2)

  • Solve the parentheses and exponents   (5-2^2) 5-4 =1

10-9+8×6÷1

  • Solve any multiplication   8×6 =48

10-9+48÷1

  • Solve any division   48÷1 =48

10-9+48

  • Solve any addition   -9+48 =39

10+39

  • Solve 10+39

Answer:

49

Step-by-step explanation:

10 - 9 + 8 × 6 ÷ (5 - 2²)

Applying BODMAS (order of operations)

We solve what is in brackets first;

5 - 2² = 1 giving;

10 - 9 + 8 × 6 ÷ 1

We then divide to get;

10 - 9 + 8 × 6

We then multiply to get;

10 - 9 + 48

We then add to get;

58 - 9

By finally subtracting we get;

58 - 9 = 49